Mathematical modeling and numerical simulation for determining an optimized oil jet layout for spiral bevel gear lubrication. (March 2021) - Zhu, X; Dai, Y; Ma, F; Ouyang, B
In aeroengine industry, the oil jet layout significantly influences lubrication of high-speed and heavy-load transmission gears, as there is only extremely limited meshing clearance for the oil stream jetting into and an inevitable blocking effect of rotating gears. A novel mathematical model for calculating the exact impingement depth of the lubrication oil jet on the spiral bevel gear surface has been established, and it contains comprehensive and detailed design parameters for the jet nozzle layout and meshing gears. Furthermore, under different jet layout parameters conditions, computational fluid dynamic numerical simulations for oil jet lubrication of an aeronautical spiral bevel gear pair were conducted and, then, the simulation results are compared with the impingement depths based on the mathematical model. The simulation results reveal that the oil volume fraction and oil pressure on the meshing area increase with the impingement depth, validating the effectiveness and reliability of the method using the impingement depth mathematical model for evaluating oil jet lubrication. Optimized oil jet layout parameters including the jet nozzle position, jet elevation angle, and jet azimuth angle have been determined and recommended, and they provide valuable theoretical design methods and technical guidance for oil jet lubrication optimization for various practical high-speed and heavy-load spiral bevel gears.